MENINGKATKAN KOMPETENSI MATA PELAJARAN PRODUKTIF INSTALASI PENERANGAN LISTRIK MELALUI PRAKTIKUM INDIVIDUAL: SMKN 1 SITUBONDO - VERY SUKARELA (Dewan Pendidikan Bondowoso, 2023)
This classroom action research aims to improve the competence of the electric lighting installation subject. This researcher used a qualitative approach because in taking action on research subjects, what was prioritized was expressing meaning; namely the meaning and process of learning as an effort to increase motivation, enthusiasm and learning achievement through actions taken (Wahid Murni et al. 2010). The type of research used was school action research (PTK). This school action research was carried out at SMK Negeri 1 Situbondo which is located at Jalan. Baluran No.17, Kotakan Utara, Kotakan, Kec. Situbondo, Situbondo Regency, East Java 68313 This research was carried out for 3 months, from September 2020 to November 2020. The research subjects were students of class XI in electrical power installation engineering (TITL) SMK Negeri 1 Situbondo in the odd semester of the 2020/20001 academic year. Data collection techniques in classroom action research (CAR) are carried out in the form of tests and non-tests. However, in this CAR, what is used is in the form of a test, namely the initial test (pre-test) and the final test (post-test) to obtain data about student learning competencies. students in the learning process by applying practicum individually. Based on the results of classroom action research that has been done, it can be concluded that 1). By carrying out individual practicums in the subject of electric lighting installation, it turns out that it can increase the learning competence of class XI students of Electrical Power Installation Engineering at SMK Negeri 1 Situbondo. 2). Carrying out practicum individually can provide an opportunity for each student to carry out practical activities installing electric lighting installations, so that each student can improve their learning competence